2013
DOI: 10.1007/s00246-013-0856-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Outcome, Valve Dysfunction, and Progressive Aortic Dilation in a Pediatric Population With Isolated Bicuspid Aortic Valve

Abstract: The aim of this study was to explore the medium-term clinical outcome and the risk of progression of aortic valve disease and aortic dilation in pediatric patients with isolated bicuspid aortic valve (BAV). 179 pediatric patients with isolated BAV were prospectively followed from January 1995 to December 2010. Patients with severe valve dysfunction at baseline were excluded. Clinical outcome included cardiac death, infective endocarditis, aortic complications, cardiac surgery and percutaneous valvuloplasty. Ec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
33
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(36 citation statements)
references
References 39 publications
3
33
0
Order By: Relevance
“…Of note, our limited analysis of aortic growth rates in this cohort does not suggest a correlation between hemodynamics and ascending aorta growth rates. However, the number of patients with repeat studies in our cohort is relatively small, and as our data suggests and a recent study by Spaziani et al 35 reports, aortic dilation in children is a very slow process and would require longer follow-up in a larger cohort of patients to adequately assess the impact of altered hemodynamics on aortic growth rates.…”
Section: Discussionmentioning
confidence: 71%
“…Of note, our limited analysis of aortic growth rates in this cohort does not suggest a correlation between hemodynamics and ascending aorta growth rates. However, the number of patients with repeat studies in our cohort is relatively small, and as our data suggests and a recent study by Spaziani et al 35 reports, aortic dilation in children is a very slow process and would require longer follow-up in a larger cohort of patients to adequately assess the impact of altered hemodynamics on aortic growth rates.…”
Section: Discussionmentioning
confidence: 71%
“…A study by Holmes et al [12] found that the pediatric BAV population underwent greatly increased AAo growth rates compared to normal children. Another study found that pediatric patients with BAV with left–right coronary commissure fusion morphology are at increased risk for aortic root dilation and that baseline aortic annular hypoplasia predicts progressive aortic stenosis [21]. However these studies used echocardiographic data and lacked the anatomical measurements and advanced hemodynamic parameters (wall shear stress, 3-D blood flow visualization) available with 4-D flow MRI, and these measurements might provide additional insight into BAV disease progression.…”
Section: Introductionmentioning
confidence: 99%
“…Bicuspid aortic valve (BAV) has been reported as the most common congenital cardiac anomaly, affecting 0.5-2% of children population. 22,24,31,33 It is predominantly seen in males and likely that its presence has a genetic basis. 19,31 Children with BAV have the risk of the lethal cardiovascular problems i.e., aortic aneurysm.…”
Section: Introductionmentioning
confidence: 99%
“…2,19,35 Progressive dilatation of the ascending aorta or aortic root, is one of the most common complications of BAV, seen even when the valve is functionally normal. 1,15,33 Association of this complication has been validated over a large data population, 22 and the American College of Cardiology and American Heart Association recommended guidelines for managing BAV with dilated ascending aorta. 14 A number of the studies reported aortic aneurysm as a serious complication of BAV with vital importance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation